KAJIAN PEMANFAATAN AIR ASAM TAMBANG UNTUK MENGAIRI AREAL PERSAWAHAN DI WILAYAH KECAMATAN KINTAP, KABUPATEN TANAH LAUT, PROVINSI KALIMANTAN SELATAN - Jarwanto, Jarwanto Jarwanto (Innofarm:Jurnal Inovasi Pertanian, 2021)
Coal mining activities that open land can cause various technical problems. Acid mining water formed due to mining activities with an area of 32.8 Ha causes a low pH to almost touch number 4 which is in the mining working pool (sump). The need to handle acid mine drainage in order to comply with quality standards. In addition, water from mining can be used by the local community. The construction of the sediment pond is placed 30 meters above the mining work area, by pumping it using a 6 "hose, then it is flowed into the sediment pond with dimensions of 14 m x 14 m per compartment with a depth of 4 meters, as many as 3 compartments. There is runoff of 2,295 m3 based on actual data. In compartment 1, the dredging is carried out every 4 months because of the sedimentation of 534.68 seconds using heavy equipment. Whereas in the second compartment, it is neutralized with 80.55 kg of lime for 2,684,090 liters of water. The third compartment obtained water clarity with laboratory tests that have been carried out so that it is close to the standard grade. Water that is ready and suitable to flow out of the sediment pond area is used to irrigate the rice fields which are 1 km from the sediment pond. Previously, the paddy fields were only once a year for harvesting. However, after there is a flow from this mining area, the rice fields can harvest the results 2 times a year and it is no longer dependent on the intensity of the rain.